A Hybrid System Dynamics and Fuzzy Logic Approach to Social Problem of Corruption in Colombia (2017)
This paper presents a system dynamics approach to the corruption problem in Colombia. The main causes were identified in service systems and their relation to drug trafficking. Each of these problems were modeled following the System Dynamics methodology, building causal diagrams and the simulation models that represent the dynamics of the factors that influence corruption such as: economic, political, social, psychological, and cultural factors. These factors are integrated in a general simulation model involving fuzzy logic in the inputs, which allows validating the behavior modeled and identify aspects to reducing the corruption in Colombia.